2022
DOI: 10.1093/jat/bkac089
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Amphetamines in Urine Drug Screens: A 6-Year Review

Abstract: Immunoassays are routinely used to provide rapid urine drug screening results in the clinical setting. These screening tests are prone to false positive results and ideally require confirmation by mass spectrometry. In this study, we have examined a large number of urine specimens where drugs other than the amphetamines may have caused a false positive amphetamine immunoassay screening result. 12,250 urine drug screens in a clinical laboratory that used the CEDIA amphetamine/ecstasy method were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…-False positive results of common medicines in drug tests.... example, metoprolol was the sixth most frequently sold drug in the United States in 2020, with over 15 million patients. This underscores the need for further investigation into the potential cross-reactivity of other beta antagonists with drug tests [5,10,13,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-False positive results of common medicines in drug tests.... example, metoprolol was the sixth most frequently sold drug in the United States in 2020, with over 15 million patients. This underscores the need for further investigation into the potential cross-reactivity of other beta antagonists with drug tests [5,10,13,32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, atenolol and bisoprolol have been found to produce F/P results in amphetamine CEDIA tests [10]. This indicates that individuals undergoing antihypertensive therapy with beta-antagonists, particularly pregnant women taking labetalol, are at a higher risk of experiencing false positive amphetamine results.…”
Section: Cardiovascular Medicationsmentioning
confidence: 99%
“…Knowledge about cross-reactivities in drug tests was not widespread based on the results of the survey, even though false-positive results due to interacting substances are well described, mainly for the amphetamine component of drug screening immunoassays [ 23 ]. The antidepressants trazodone and bupropion, the H2-antihistamine ranitidine, and stimulants such as ephedrine or methylphenidate are among the substances that can cross-react with amphetamines in immunoassays [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that amphetamine immunoassays are subject to a roughly 4% to 10% false positive rate. 255 Confirmatory testing for amphetamines can rule out false positive from other drugs (eg, bupropion, MPH, pseudoephedrine). 256 Clinicians should refer to the test manufacturer and/or consult with their laboratory to determine the capabilities and cross-reactivity of specific assays.…”
Section: Toxicology Testingmentioning
confidence: 99%
“…As discussed in ASAM’s Appropriate Use of Drug Testing in Clinical Addiction Medicine consensus statement, there are known limitations to urine immunoassays for amphetamines, and providers should be cautious when interpreting their results. A recent review found that amphetamine immunoassays are subject to a roughly 4% to 10% false positive rate 255 . Confirmatory testing for amphetamines can rule out false positive from other drugs (eg, bupropion, MPH, pseudoephedrine) 256 .…”
Section: Assessment and Diagnosismentioning
confidence: 99%